Characteristics of Several Qualitative Traits of Betet Chickens Raised by Fighting Cock Fans in Central Lombok - Tamzil, M.H.; Indarsih, B.; Jaya, N. S.; Haryani, N. K. D.; Asnawi, A. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The study was conducted to determine the characteristics of betet chickens kept by fighting cock enthusiasts in Central Lombok. Determining the research area was carried out using the cluster sampling method, and sampling of farm was carried out non-randomly using the snowball method, and determining the number of chicken samples for observation was carried out using the accidental sampling method. Observations were made on 74 male Betet and 26 female Betet birds The variables observed were: body posture, feather color, beak color, beak shape, shank color and comb shape. The data obtained were tabulated, the frequency was calculated and analyzed using descriptive analysis. The results of the research found that the feather color of male betet chickens was dominated by bing (black), followed by green, brumbun and the smallest frequency of lurik colors. The feather color of female betet chickens was dominated by the alap color, followed by the kelawu color and the lowest frequency of the berumbun color. The highest frequency of beak color was yellow, followed by black, and the majority was sharply curved. The highest frequency of shank color in male betet chickens was yellow, followed by black and the lowest frequency was white. There were no white shanks found in female betet birds. The highest frequency of the comb shape for male betet chickens was without a comb because it is cut, followed by the single shape, then the lowest frequency was the pea shape. The majority of female betet chickens have a single comb, the rest do not have a comb (the comb does not develop). It was concluded that betet chickens kept by fighting cock enthusiasts